(No^ERKI PO ISTORII GARMONII W RUSSKOJ I MUZYKE(B.s (NwYPUSK (BIIs ((NmOSKWAs (NMUZYKA s, 1985)
(NwTIOROJ WYPUSK WKL@^AET O^ERKI PO^WQ]ENNYE GARMONII KOMPOZITOROW (B"(NMogu~ej ku~ki(B"-(NbORODINA mUSORSKOGO rIMSKOGO(B-(NkORSOKOWA(B.s
Keywords: (NtEORIQ(B.s